(untitled) (Indonesian Sports Justice Review, 2025)
Indigenous athletes in Indonesia face unique challenges related to recognition, representation, and inclusion in national sports teams. This paper explores how indigenous athletes are represented in mainstream sports, the support they receive from sports organizations, and the cultural barriers they encounter. It critically examines the intersection of ethnicity, identity, and sports justice, focusing on how the lack of cultural recognition can lead to exclusion and marginalization in Indonesia’s sports landscape. Through interviews with indigenous athletes, coaches, and sports administrators, the paper assesses the barriers to equal participation and suggests ways to promote greater inclusion of indigenous athletes in national sports programs. The paper argues for a more culturally sensitive and equitable approach to sports governance in Indonesia.